2015
DOI: 10.1186/s12884-015-0672-3
|View full text |Cite
|
Sign up to set email alerts
|

Why do women invest in pre-pregnancy health and care? A qualitative investigation with women attending maternity services

Abstract: BackgroundDespite the importance attributed to good pre-pregnancy care and its potential to improve pregnancy and child health outcomes, relatively little is known about why women invest in pre-pregnancy health and care. We sought to gain insight into why women invested in pre-pregnancy health and care.MethodsWe carried out 20 qualitative in-depth interviews with pregnant or recently pregnant women who were drawn from a survey of antenatal clinic attendees in London, UK. Interviewees were purposively sampled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 54 publications
4
35
0
Order By: Relevance
“…It is possible that many strategies acting synergistically are needed to improve service delivery. This is consistent with findings from a qualitative study (11), which showed that women who take a micronutrient supplement are more likely to invest in their preconception health and care. The authors identified women belonging to three groups—the ‘prepared’ group, the ‘poor knowledge’ group, and the ‘absent pre-pregnancy’ group—and argued that different preconception strategies are needed to target different women.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is possible that many strategies acting synergistically are needed to improve service delivery. This is consistent with findings from a qualitative study (11), which showed that women who take a micronutrient supplement are more likely to invest in their preconception health and care. The authors identified women belonging to three groups—the ‘prepared’ group, the ‘poor knowledge’ group, and the ‘absent pre-pregnancy’ group—and argued that different preconception strategies are needed to target different women.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies (11,18) have found a low knowledge of behaviours related to preconception care and a need to increase general awareness. Women who receive preconception counselling are more likely to adopt healthier behaviours before pregnancy, leading to an improved diet, folic acid supplementation, and cutting down or stopping smoking (10,27).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Another aspect with great relevance in women's decision to take preparation measures during the preconception period is their knowledge about importance of preconception health, which, in turn, is related to schooling. In fact, a study carried out in London, England, with women undergoing planned pregnancies showed that knowledge about preconception care favors it realization (27) .…”
Section: Discussionmentioning
confidence: 99%
“…While it is possible to change unhealthy lifestyle factors, to reduce or even eliminate them to help couples to conceive, adherence with these recommendations could be improved through greater awareness among health professionals in primary care and fertility clinics (Joelsson et al, 2016). However, how effective preconception interventions can best be delivered, and whether specific recommendations change behaviour (Anderson et al, 2010;Barret et al, 2015;Shawe et al (2015)) and who should deliver preconception interventions (Hemsing et al, 2017;Kelly-Weeder & O'Connor, 2006) are future research questions.…”
Section: Discussionmentioning
confidence: 99%